Numerical Investigations of a Silicon Photonic TE-Pass Polarizer Consisting of Alternating Copper/Silicon Nitride Layers - Lei Chen; Han Ye; Yumin Liu; Dong Wu; Rui Ma; Zhongyuan Yu (IEEE Photonics Journal, 2017)
We propose and investigate a silicon photonic TE-pass polarizer consisting of alternating layers made out of copper/silicon nitride (Cu/Si3N4). Based on a Si stripe waveguide, the launched dominant fundamental TE mode can normally pass through it with little influence, whereas the unwanted fundamental TM mode ends up in nearly zero output as it is gradually coupled into a plasmonic mode. Particularly, the polarizer with wedge-shaped Cu/Si3N4 structure can achieve extremely high extinction ratio (ER) of 52.34 dB and low insertion loss of 0.35 dB within an ultracompact device length of 2 μ m. It also presents a relatively wide operating bandwidth of 61 nm maintaining ER >20 dB. Furthermore, considering Si3N4 itself a good Cu2+ ion diffusion barrier and its good adhesion to copper, the device fabrication is reasonably practicable using complementary metal–oxide semiconductor (CMOS)-compatible technologies. Last but not the least, we first present and analyze the connection between mode property and device performance, which could provide a significant step forward for establishing and improving the polarization diversity systems of great importance in nanophotonic integrated circuits.